Tibial Tubercle Apophyseal Stage to Determine Skeletal Age in Pediatric Patients Undergoing ACL Reconstruction: A Validation and Reliability Study. Issue 9 (2nd September 2021) - Dekhne, Mihir S.; Kocher, Isabelle D.; Hussain, Zaamin B.; Feroe, Aliya G.; Sankarankutty, Saritha; Williams, Kathryn A.; Heyworth, Benton E.; Milewski, Matthew D.; Kocher, Mininder S.
Background: Anterior cruciate ligament (ACL) injuries demand individualized treatments based on an accurate estimation of the child's skeletal age. Wrist radiographs, which have traditionally been used to determine skeletal age, have a number of limitations, including cost, radiation exposure, and inconvenience. Purpose: To evaluate the reliability and validity of a radiographic staging system using tibial apophyseal landmarks as hypothetical proxies for skeletal age to use in the preoperative management of pediatric ACL tears. Study Design: Cohort study (diagnosis); Level of evidence, 2. Methods: The study included children younger than 16 years of age who underwent ACL reconstruction between July 2008 and July 2018 and received both skeletal age radiography and knee radiography within 3 months of each other. Skeletal age was calculated from hand and wrist radiographs using the Greulich and Pyle atlas. Tibial apophyseal staging was categorized into 4 stages: cartilaginous stage (stage 1), apophyseal stage (stage 2), epiphyseal stage (stage 3), and bony/fused stage (stage 4). Data were collected by 2 independent assessors. The analysis was repeated 1 month later with the same assessors. We calculated descriptive statistics, measures of agreement, and the correlation between skeletal age and apophyseal stage. Results: The mean chronological age of the 287 patients included in the analysis was 12.9 ± 1.9 years; 164 (57%) of the patients were male. The overall Spearman r between skeletal age and tibial apophyseal staging was 0.69 (0.77 in males; 0.60 in females). The interrater reliability for the tibial apophyseal staging was substantial (Cohen κ = 0.66), and the intrarater reliability was excellent (Cohen κ = 0.82). The interrater reliability for skeletal age was excellent (intraclass correlation coefficient [ICC] = 0.93), as was the intrarater reliability (ICC = 0.97). Conclusion: The observed correlation between skeletal age and tibial apophyseal staging as well as observed intra- and interrater reliabilities demonstrated that tibial apophyseal landmarks on knee radiographs may be used to estimate skeletal age. This study supports the validity of knee radiographs in determining skeletal age and provides early evidence in certain clinical presentations to simplify the diagnostic workup and operative management of pediatric knee injuries, including ACL tears.